1996
DOI: 10.1121/1.417051
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in consonant confusion

Abstract: Both historical sound change and laboratory confusion studies show strong asymmetries of consonant confusions. Historically [ki] commonly changes to [t∫i] (e.g., English chill, cognates with cool), but not the reverse. Similarly, Winitiz et al. [J. Acoust. Soc. Am. 51, 1309–1317 (1972)] in a consonant confusion study, found [ki] confused with [ti] more often than the reverse. It is hypothesized that such asymmetries arise when two sounds are acoustically similar except for one or more differentiating cues, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The confusion rates for these sounds are asymmetric; for example, [ki] was identified as [t ʃi] 3.5 times more frequently than [t ʃi] was identified as [ki]. Such asymmetries are commonly found in identification experiments (Nosofsky, 1991;Ohala, 1997;Plauché, Delogu, & Ohala, 1997;Tversky, 1977). Although not of central interest for this article, the observed asymmetries do have some consequences, discussed in section 3, for formal modeling of the confusion data.…”
Section: Notesmentioning
confidence: 95%
See 1 more Smart Citation
“…The confusion rates for these sounds are asymmetric; for example, [ki] was identified as [t ʃi] 3.5 times more frequently than [t ʃi] was identified as [ki]. Such asymmetries are commonly found in identification experiments (Nosofsky, 1991;Ohala, 1997;Plauché, Delogu, & Ohala, 1997;Tversky, 1977). Although not of central interest for this article, the observed asymmetries do have some consequences, discussed in section 3, for formal modeling of the confusion data.…”
Section: Notesmentioning
confidence: 95%
“…2. I take the absolute limits on human phonologies to be not substantive, but rather set by formal properties of the type investigated within optimality theory by Albro (2005), Eisner (1997), and Riggle (2004) and within rule-based phonology by, for example, Reiss (2003 (Nosofsky, 1991;Ohala, 1997;Plauché, Delogu, & Ohala, 1997;Tversky, 1977). Although not of central interest for this article, the observed asymmetries do have some consequences, discussed in section 3, for formal modeling of the confusion data.…”
Section: Notesmentioning
confidence: 99%
“…However, as has been amply revealed in perception studies, perceptual confusion is very often asymmetric. For example, Guion (1998) found that when listening conditions were artificially degraded so as to increase confusion rates, misidentifications of /ki/ as /i/ occurred three to four times as often as the converse confusions (/i/ heard as /ki/), which were quite rare (see also Plauché et al. 1997; Winitz et al.…”
Section: The Listener‐based Model Of Sound Changementioning
confidence: 99%
“…For example, in visual letter recognition, one is far more likely to misperceive a ‘Q’ as ‘O’ (by failing to notice the distinctive tail that sets the former apart from the latter) than to misperceive ‘O’ as ‘Q’ (by spuriously introducing that same characteristic feature). Plauché et al. (1997) suggest that the /ki/ vs. asymmetry is due to precisely such an all‐or‐nothing feature in the acoustic signal, namely, the spectral peak in the 3–4 kHz range that is characteristic of velars.…”
mentioning
confidence: 99%
“…Without these unique acoustic-phonetic cues, /k/ perceptually resembles /p/ and /t/, but /p/ and /t/ in the presence of noise would not be mistaken for /k/. Perceptual studies show support for such an explanation in the case of the observed asymmetric pattern favoring /ti/ over /ki/ [Plauché et al, 1997;Chang et al, 2001;Plauché, 2001]. In the account given in those reports, listeners may occasionally fail to perceive a midfrequency burst when presented with /ki/, resulting in the perception of /ti/, but listeners will rarely if ever hallucinate a mid-frequency burst when presented with /ti/, and will therefore rarely report /ki/.…”
Section: Asymmetrical Confusions In Consonantsmentioning
confidence: 63%